Solubility of Carbamazepine-Succinic Co-Crystal in Ethanolic Solvent System - Noor Ashila, Ramle; Syarifah, Abd Rahim; El-Hadad, Omar; Nornizar, Anuar (Trans Tech Publications, Switzerland, 2015)
Solubility of carbamazepine co-crystal produced from cooling co-crystallization process with succinic acid as a co-crystal former is investigated in this study. Two techniques are used to determine the solubility of the co-crystal which is gravimetric and HPLC.The solubility experiment in ethanol solvent system were conducted at 6 different temperatures (25, 30, 35, 40, 45 and 50°c) while for succinic acid solution system were conducted at 5 different concentration ratio. Both of the system are equilibrated for 72 hours. Result from the experiment has shown that the solubility of co-crystal is depending on temperature. As the temperature increase, the solubility of co-crystal also increased, this situation meets the Second Law of Thermodynamic which heat facilitates the dissolution process by providing more energy to the system.